The constitutional systems of the Australian states and territories / Gerard Carney. - Carney, Gerard (Cambridge University Press, 2006)
This book outlines the constitutional systems of the six Australian states and ten Commonwealth territories. It begins with their history, basic features, role and future within the Australian federation. Its primary focus is on the binding constitutional restrictions which impact on their parliaments and governments. These issues are also dealt with in relation to the three self-governing territories of the ACT, the Northern Territory and Norfolk Island. It is the only Australian legal reference work of its kind which deals specifically with the constitutional systems of the states and territories. This book is for all law students and constitutional law teachers as well as legal advisors to commonwealth, state and territory governments and parliaments. It will also be of interest to Supreme, Federal, and High Court judges, political scientists working in the area of federalism and anyone with an interest in constitutional affairs.